Method of determining the value of information assets of the organization - Кобрин, Максим Витальевич; Скичко, Владимир Владимирович (Ukrainian Information Security Research Journal, 2015)
The development and implementation of optimal practicesto protect and manage information assets, effective allocation resources of the company is possible with theright of determining the value of information assets.Knowledge Management Specialists consider informationassets as part of the intellectual capital and offer, as a rule,quantitative methods for its measurement related to valuation.This approach is not effective in the safety management systems of information assets. To solve theproblem of estimating the information assets of the organizationare offered to adapt the method of ordinal classification. Using this method allow formalize the definitionof the value of the information asset that will provide universal nature of valuation, will take into accountin the selection criteria for the specifics of the organizationand priorities of persons engaged in security managementof information assets.